2013
DOI: 10.1007/s10482-013-9888-2
|View full text |Cite
|
Sign up to set email alerts
|

Micromonospora avicenniae sp. nov., isolated from a root of Avicennia marina

Abstract: Strain 268506(T) was isolated from a root of Avicennia marina collected at mangrove forest in Wengchang, Hainan province, China. The 16S rRNA gene sequence of strain 268506(T) showed the highest similarity with Micromonospora equina Y22(T) (98.8 %) and Micromonospora olivasterospora DSM 43868(T) (98.7 %). In addition, gyrB gene phylogeny clearly showed strain 268506(T) should be assigned to the genus Micromonospora but different from any established Micromonospora species. The predominant menaquinones are MK-9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The description is as before (Li et al, 2013 ) with the following modification. The G+C content of the type-strain genome is 71.5%, its approximate size 6.82 Mbp, its GenBank deposit SAMN05444858 .…”
Section: Discussionmentioning
confidence: 99%
“…The description is as before (Li et al, 2013 ) with the following modification. The G+C content of the type-strain genome is 71.5%, its approximate size 6.82 Mbp, its GenBank deposit SAMN05444858 .…”
Section: Discussionmentioning
confidence: 99%
“…We also found that the interaction between N. attenuata and S. arenicola resembled that of plant-endophytic symbiosis ( Figure 5A). Other actinobacteria (i.e., Micromonospora and Verrucosispora) from the same family of the coral symbiont Salinispora have been isolated from the root nodules of terrestrial and marine plants where they presented endophytic interactions and conferred advantages to their plant hosts (Figure 2; Li et al, 2013;Ngaemthao et al, 2017;Kuncharoen et al, 2018). Bioinformatic analysis suggests that Salinispora spp.…”
Section: Discussionmentioning
confidence: 99%
“…The morphological characteristics of strain 2902at01 T were assessed by scanning electron microscopy (TM 3000; Hitachi) using 7-day-old cultures on ISP 2 agar. Cultural characteristics of strain 2902at01 T were determined on various agar media including ATCC 172 agar, Czapek's agar, ISP 1–7 agar, MB agar, and potato-glucose agar as previously used (Li et al , 2013a), and M8 agar (Castiglione et al , 2008) and nutrient agar (Waksman, 1967). The ISCC-NBS colour chart was used to determine the names and designations of colony colours (Kelly, 1964).…”
mentioning
confidence: 99%
“…Analysis of phospholipids was carried out using TLC according to Minnikin et al (1984). Fatty acids were extracted from fresh cells obtained with the same cultural conditions above using the method of Sasser (1990) and the composition was determined by GC-MS performed on a GC instrument (Li et al 2013a). Menaquinones were extracted from freeze-dried biomass, purified according to Minnikin et al (1984) and finally analysed by HPLC with an ODS-BP C18 column (4.66250 mm); the elution solvent was methanol and 2-propanol (3 : 2, v/v) based on the method of Li et al (2013a).…”
mentioning
confidence: 99%